Challenges in Estimating Characteristics of Staphylococcus aureus Nasal Carriage Among Humans Enrolled in Surveillance Studies - Thanh-Thao Le; Maya Nadimpalli; Jianyong Wu; Christopher D. Heaney; Christopher D. Heaney; Christopher D. Heaney; Jill R. Stewart (Frontiers Media S.A., 2018)
Evaluating carriage of Staphylococcus aureus, an opportunistic pathogen of humans and animals capable of causing antibiotic-resistant infections, is epidemiologically important. However, clinical and epidemiological surveillance studies of S. aureus typically rely on characterizing one isolate per individual, which may not represent the actual population diversity in a carrier. The objective of this study was to determine if one isolate is sufficient for determining carrier status of particular strains or characteristics of S. aureus in a healthy (non-hospitalized) human population. We compared spa types, genetic markers (mecA, scn), and antibiotic resistance profiles of 10 S. aureus isolates recovered from a single nasal swab for each of 19 participants (190 isolates total) selected from a cohort of industrial hog operation workers and their household members. Participants included both persistent (n = 10) and intermediate (n = 9) carriers of S. aureus. Among the participants, 17 (89%) carried a single S. aureus spa type intranasally and the other two carried dominant spa types. Less similarity was observed for genes encoded on mobile genetic elements (mecA, scn) and antibiotic resistance profiles. Statistical modeling, based on receiving operating characteristic curves, suggests that three to five isolates may be necessary to accurately assign nasal carriage status for these more variable characteristics. Variability was observed for both persistent and intermediate carriers of S. aureus. These results suggest that surveillance studies that rely on testing one S. aureus isolate are likely to identify predominant spa types but may not fully capture more variable characteristics of S. aureus, including antibiotic resistance. Surveillance studies that rely on testing one isolate may underestimate prevalence of nasal carriage of S. aureus with these more variable characteristics.